Denitrification accelerates granular sludge formation in sequencing batch reactors. (November 2015) - Suja, E.; Nancharaiah, Y.V.; Krishna Mohan, T.V.; Venugopalan, V.P.
Graphical abstract: Highlights: Denitrification facilitated rapid formation of aerobic granular sludge in SBRs. Nitric oxide signaling and CaCO3 formation were hypothesized to assist granulation. NO donor (sodium nitroprusside) promoted EPS production and sludge granulation. CaCO3 precipitates increase density of granules. CaCO3 precipitates may act as nucleation sites for granulation. Abstract: In this study, the role of denitrification on aerobic granular sludge formation in sequencing batch reactors (SBRs) was investigated. Formation of aerobic granular sludge was faster in SBRs fed with varying concentrations of nitrate or nitrite as compared to control, which received no nitrate or nitrite in the feed. The majority of the fed nitrate or nitrite was denitrified in the anoxic static fill phase, prior to aerobic reaction phase. Sludge characterization showed accumulation of calcium and chemical signature of calcium carbonate in the nitrate-fed SBRs. Feeding of sodium nitroprusside, a known nitric oxide (NO) donor, enhanced aggregation, production of extracellular polymeric substances and formation of aerobic granular sludge. The results support the hypothesis that denitrification facilitates cell aggregation and accelerates aerobic sludge granulation through NO signaling and CaCO3 formation. Nitrate or other intermediates of heterotrophic denitrification, therefore, have a positive effect on aerobic granulation in SBRs.